Reliability, sensitivity and validity of the assistant referee intermittent endurance test (ARIET) - a modified Yo-Yo IE2 test for elite soccer assistant referees - Castagna, C.; Bendiksen, M.; Impellizzeri, F. M.; Krustrup, P. (Journal of Sports Sciences, 2012)
We examined the reliability and validity of the assistant referee intermittent endurance test (ARIET), a modified Yo-Yo IE2 test including shuttles of sideways running. The ARIET was carried out on 198 Italian (Serie A-B, Lega-Pro and National Level) and 47 Danish elite soccer assistant referees. Reproducibility was tested for 41 assistant referees on four occasions each separated by one week. The ARIET intraclass correlation coefficients and typical error of measurement ranged from 0.96 to 0.99 and 3.1 to 5.7%, respectively. ARIET performance for Serie A and B was 23 and 25% greater than in Lega-Pro (P < 0.001). The lowest cut-off value derived from receiving operator characteristic discriminating Serie A-B from Lega-Pro was 1300 m. The ARIET performance was significantly correlated with [Vdot]O2max (r = 0.78, P < 0.001), %HRmax after 4 min of ARIET (r = - 0.81, P < 0.001) and Yo-Yo IR1 performance (r = 0.95, P < 0.001), but not sprint performance (r = -0.15; P = 0.58). The results showed that ARIET is a reproducible and valid test that is able to discriminate between assistant referees of different competitive levels. The lack of correlation with sprinting ability and close correlations with aerobic power, intermittent shuttle running and sub-maximal ARIET heart rate loading provide evidence that ARIET is arelevant test for assessment of intermittent endurance capacity of soccer assistant referees.